(untitled) (The Peerian Journal, 2024)
This study explores the complicated relationships between gum inflammation severity, inflammatory markers (IL-6 and CRP), and fasting blood sugar levels, linking oral and systemic health. A study of mild, severe, and moderate gum inflammation groups found significant differences in IL-6, CRP, and fasting blood sugar. IL-6 levels are much greater in severe gum inflammation, indicating inflammation. Additionally, severe gum inflammation raises CRP, suggesting a systemic inflammatory response to periodontal disease. Fasting blood sugar differs for severe and mild gum inflammation. This disparity indicates glucose metabolism issues and oral-systemic health. Chronic inflammation and reduced insulin sensitivity from severe gum disease increase fasting blood sugar and diabetes risk. These findings emphasize dental-systemic health. Monitor gum inflammation patients’ IL-6, CRP, and fasting blood sugar to assess severity and systemic consequences, the study’s bidirectional relationship may enhance health outcomes through focused interventions, preventive measures, and collaborative healthcare.